2023
DOI: 10.1097/js9.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for achieving textbook outcome after laparoscopic duodenum-preserving total pancreatic head resection: a retrospective cohort study

Abstract: Introduction: The risk factors for achieving textbook outcome (TO) after laparoscopic duodenum-preserving total pancreatic head resection (LDPPHR-t) are unknown, and no relevant articles have been reported so far. The aim of this study was to identify the risk factors for achieving TO after LDPPHR-t. Methods: The risk factors for achieving TO after LDPPHR-t were retrospectively evaluated by logistic regression analysis in 31 consecutive patients from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Interestingly, we found statistically significant differences between the two groups in laboratory test results on the third day after surgery (including the proportion of neutrophils, amylase levels in drainage fluid, and other factors related to POPF). This suggests that POPF is a critical postoperative complication to be concerned about, which is consistent with the current high-priority scientific issues in PD ( 24 , 46 ). POPF is likely to act as a focal point and trigger for other postoperative complications, such as abdominal infections and PPH.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, we found statistically significant differences between the two groups in laboratory test results on the third day after surgery (including the proportion of neutrophils, amylase levels in drainage fluid, and other factors related to POPF). This suggests that POPF is a critical postoperative complication to be concerned about, which is consistent with the current high-priority scientific issues in PD ( 24 , 46 ). POPF is likely to act as a focal point and trigger for other postoperative complications, such as abdominal infections and PPH.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, the researchers used TO as a primary indicator to evaluate the short-term surgical outcomes of Laparoscopic duodenum-preserving pancreatic head resection (LDPPHR-t) and found that POPF was the primary barrier to achieving TO after LDPPHR-t. Placement of an endoscopic nasobiliary drainage (ENBD) tube was recognized as the only significant independent risk factor for developing POPF following LDPPHR-t surgery. Their researches used TO to explore possible avenues for improving the quality of PD ( 24 ). The widespread adoption of neoadjuvant therapy in unresectable pancreatic ductal adenocarcinoma (PDAC) has made pancreatic surgery more complex and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic stula is the most important complication after DPPHR [21,22]. A soft texture of the pancreas and a diameter of the pancreatic duct less than 3 mm in benign pancreatic tumors are the main risk factors for pancreatic stula [23,24]. In addition, residual pancreatic tissue is also a potential risk factor for pancreatic stula.…”
Section: Discussionmentioning
confidence: 99%